Modelling and optimization of PVDF based surface acoustic wave MEMS microphone. (2021) - Karbari, Sudha R.; Uttara Kumari, M.; Shireesha, G.
Abstract: A detailed finite element simulations of a piezoelectric based biomimetic surface acoustic wave device as MEMS Microphone is analyzed. A symmetric piezoelectric PVDF based MEMS Microphone inspired by Ormia Orchea provides an excellent frequency response for four resonant frequency bands 84.051 K Hz, 134.25 K Hz, 134.4 K Hz and 137.8 K Hz. The device is actuated in two different modes, bending and rocking mode and its sound pressure field and absolute pressure is analyzed for its structural properties. The signal mapping and transduction method for the MEMS microphone is achieved by incorporating four Inter Digited Electrodes along the wings of the biomimetic structure stacked on piezoelectric membrane guiding the surface acoustic waves along the membrane. The maximum sound pressure level of 381.2 dB is attained at 820 µm at the center of the membrane and a spatial distribution of surface pressure to a value of 4.31 × 10 −11 Pa for 84.041 KHz. The design with its functionality is apt for fabrication with the stacked nanomaterials.